Sistem Informasi Monitoring Data Administrasi (Persuratan) Berbasis Web pada UPTD SMAN 3 Menggunakan QR Code - Husni Husni; Reski Idrus; Sapriadi Sapriadi; Basri Basri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Correspondence administration is vital for supporting operational efficiency in schools. However, manual management often leads to issues such as data retrieval delays, recording errors, and the risk of lost archives. This research aims to design and develop a Web-Based Administration Data Monitoring Information System using QR Codes at UPTD SMAN 3 Majene. The study employs the Research and Development (R&D) method with the Waterfall model, encompassing requirements analysis, system design, implementation, testing, and maintenance.The system involves three primary users: Admin/Administrative Staff, Teachers, and the Principal. QR Codes are implemented as digital identities to facilitate easier archive tracking and retrieval. Results indicate that the system enhances effectiveness and efficiency in correspondence management, accelerates letter request services, and simplifies data monitoring for school management. This system is expected to provide a solution for achieving orderly administration at UPTD SMAN 3 Majene. Furthermore, QR Code integration ensures document validity and digital archive security, supporting a more modern, transparent, and sustainable school governance transformation.